2015
DOI: 10.1007/s13197-015-1754-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of blend moisture and extrusion temperature on physical properties of everlasting pea-wheat extrudates

Abstract: The effect of everlasting pea in combination with wheat on physical properties and microstructure of extrudates were studied. The share of everlasting pea (Lathyrus sativus) was variable, at 35, 50 and 65 %, respectively. The everlasting pea-wheat mixtures were moistened to the required level (18, 21, and 24 %), homogenized, conditioned and extruded in twin-screw extruder with counter-rotating conical screws. All of the obtained extrudates were characterised by a slow degree of radial expansion and high specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…So that the SME was increased significantly when blending PPP with WG ( P < 0.05). Particularly, it increased from 836.40 to 881.82 kJ kg −1 ( P < 0.05) when the ratio of WG increased from 20% to 60%, which might be due to the viscosity increased and screw wear brought by the WG (Zarzycki et al ., ). The increase in the viscosity also indicated that higher degree of aggregation might occur in the PPP‐WG mixtures, which could entrap more water due to the greater effective volume of the aggregates (Zhang et al ., ; Wang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…So that the SME was increased significantly when blending PPP with WG ( P < 0.05). Particularly, it increased from 836.40 to 881.82 kJ kg −1 ( P < 0.05) when the ratio of WG increased from 20% to 60%, which might be due to the viscosity increased and screw wear brought by the WG (Zarzycki et al ., ). The increase in the viscosity also indicated that higher degree of aggregation might occur in the PPP‐WG mixtures, which could entrap more water due to the greater effective volume of the aggregates (Zhang et al ., ; Wang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…When making a comparison of the results of EI and density, it can be stated that achieving a very low density does not necessarily imply a maximum expansion, as observed in Figures 3A, 4A, where the highest level of increase was completed at the point hydrolyzed protein flour 30% and moisture content 16%. Density and EI were negatively correlated in any extrusion process, behavior related to the distribution of cells inside the extrudate, size, and thickness of the walls that they form makeup (Zarzycki et al, 2015).…”
Section: Densitymentioning
confidence: 96%
“…The effect of extruder feed moisture content on the breaking force of extrudates has been widely studied (Liu, Hsieh, Heymann, & Huff, ; Seth, Badwaik, & Ganapathy, ; Zarzycki et al., ). At a higher feed moisture content, the viscosity of the dough and mechanical energy in the extruder decreased, stopping the bubble growth at temperatures below the glass transition temperature (Kristiawan, Chaunier, Della Valle, Ndiaye, & Vergnes, ).…”
Section: Resultsmentioning
confidence: 99%